Explanatory priority and independence: On an argument against middle knowledge - Dekker, Eef (Sophia, 1999)
A Molinist should not embrace the independence thesis. He also can defend the thesis that counterfactuals of freedom depend on a counterfactual act. Although such a move may seem illicit in the sense thatexplanandum andexplanans presuppose each other, I defend the view that counterfactuals of freedom are very deeply embedded in our metaphysics and we cannot therefore satisfactorily explain them with the help of other devices.